Political Consciousness Formation in the Modern Global World - V. Balakhonsky, Vitaly; D. Shipunova, Olga; I. Strelchenko, Vasiliy; V. Balakhonskaya, Liudmila; V. Beresneva, Iuliia (International Journal of Criminology and Sociology, 2022)
The article examines an actual problem of international integration, associated with the peculiarities of political consciousness in modern global society. The research methodology is determined by the synthesis of analytical and comparative historical approaches. The authors consider such conditions of global society existence in which the objective social polarity of a society and the heterogeneity of political structures give rise to a wide range of needs and interests of groups and individuals. This feature forms the difference in the elements of their political consciousness. As a result, several forms of political consciousness can exist simultaneously in every society. Conceptual description motivational structure in sociopolitical systems requires the complex application of various bases for their classification. In conclusion, it is emphasized that real social systems are characterized by a complex synthesis of elements of various political consciousness types. The unity of diverse forms of political consciousness organization in a global society is based on an axiological meaningful consensus of socio-cultural relationships between people, between society and man, between state and man, conceptual represented in the symbols that motivate individual and group consciousness on trust in the authorities.